L’inhumation des immatures in ecclesia à l’époque moderne : l’exemple de la nef de Saint-André-le-Haut (Vienne, Isère, France) - Vanessa Granger; Otilia Stoica; Delphine Linard; Audrey Gaillard; Bérénice Chamel (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The Abbey of Saint-André-le-Haut (Vienne, Isère, France), founded by Benedictine nuns in the 6th century, is one of the city’s oldest monastic buildings. In the 16th century, the abbey church became a parish church and the parishioners consecrated the floor of its nave as a burial site. Since 2003, two-thirds of the nave of Saint-André-le-Haut have been excavated, revealing 317 burials from the early modern period. Of these, 102 are of immature individuals, including 30 in the [0] class. The presence of these individuals within the parish community, particularly inside the church, points to full integration into the Christian world. Two groups of small children stand out: the first around a pillar at the church entrance, the second beside the north lateral wall. It is possible that the presence of distinctive liturgical details in these two places is related to these groups of small children.